(untitled) (Malaysian Journal of Civil Engineering, 2020)
Over the years buildings are constructed in earthquake prone areas without following proper seismic design code. So the structural seismic analysis of existing buildings in the earthquake prone areas will be a prime requirement in the field of civil engineering in near future. Also the structural seismic analysis will lead to the feasibility of application of earthquake retrofitting technique in the vulnerable structures. Currently the urbanization of metropolitan cities in Bangladesh is booming rapidly leading these cities to densely populated area. In the past, there has been vulnerability assessment done for building stock on several metropolitan cities, in most cases using rapid visual screening (RVS) method. But the lacking has always been there on a detailed structural vulnerability assessment. Considering these facts a study has to be done to estimate precisely the possible damage of a building’s structure. In this study an in-depth structural seismic analysis of a medium rise building has been performed using all the 3 levels of Japanese Index Method. The Seismic Index (Is) value of the building is compared with the Seismic Demand Index (Iso) value which is 0.864 for the first level and 0.648 for the second and third level of the area to check vulnerability condition of the building structure. It is observed from this study that Japanese Index Method is developed in a way that it can be used for the seismic analysis of medium rise buildings in Bangladesh.